A conceptual model for car park network system. - Liang, Qipei. (2009)
With rising levels of car ownership and usage, searching for a parking space has become increasingly difficult for drivers, especially in city-centres with limited land space. The drivers’ choice of car park and the route they take to reach it are the outcomes of highly complex decision processes. To influence such choices, an important mean is to provide drivers with information. Thus we propose a Car Park Network system which provides real-time parking information to drivers through a centralized database. It is a two-way communication system for exchange of information between the operators and the end-users. The system also offers other applications such as reservation function, payment processing, car park navigation and reports and statistics. Hence, it allows end-users to make informed decisions, brings convenience, saves time and money and reduces frustration. At the same time, the car park operators can, with minimal costs, enhance their quality of service, ensure competitiveness, anticipate demand and earn additional revenue. However, as this system is sophisticated and complex, there are many potential challenges and further research needs to be done on certain area.